185k views
4 votes
-6(x + 7) = -12 Help plzzzzzz

2 Answers

5 votes

Answer:

X = -5

Explanation:

-6(x+7)=-12

Use the distributive property

-6x-42=-12

Add 42 to -42, and 42 to -12

Adding 42 to -42 cancels -42 out

-6x=30

Divide -6 by -6, and 30 by -6

x=-5

User Thwd
by
5.0k points
7 votes

Answer:

x=-5

Explanation:

-6(x + 7)=-12

-6x+-42=-12

-6x=30

x=-5

User Matt Johnson
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.